Enhancing smoked meat (Se’i sapi) quality: The impact of adding essential oils of cinnamon and lime leaf during room temperature storage. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study examines the effects of lime leaf and cinnamon essential oils (EOs) at different concentrations and storage durations on the quality of Se’i under ambient conditions. Materials and Methods: We used a two-factor completely randomized design with three replications. The first factor involved EO concentrations of 0.1%, 0.3%, and 0.5%, while the second factor was storage duration at 0, 7, 14, and 21 days. Key parameters evaluated included pH, tenderness, thiobarbituric acid values, meat color, and sensory analysis. Results: The results indicated that adding EOs effectively preserved the smoked meat, with improved quality parameters compared to the control group. Conclusion: Adding 0.5% lime leaf or cinnamon essential oil to Se'i made it taste and look much better, showing that it could be used as a natural way to keep smoked meats fresh.J. Adv. Vet. Anim. Res., 12(1): 33–43, March 2025http://doi.org/10.5455/javar.2025.l869